DI-002 Drug interactions: an example of scientific cooperation between the hospital pharmacist and general practitioners (GPS). (24th March 2015) - Vinciguerra, V; Fantozzi, R; Rolle, C
Abstract : Background: Interactions frequently occur between drugsand can generate Adverse Drug Reactions (ADRs). In 2013, pharmacists from the Local Health District joined a project with 48 General Practitioners (GPs), who chose drug combinations for which they invited monitoring of their prescriptions for interactions: verapamil + simvastatin (i1), potassium chloride + potassium canrenoate (i2), calcium carbonate + Proton Pump Inhibitors (PPIs) (i3A), sevelamer + PPIs (i3B), levothyroxine + PPIs (i3C), fluconazole + PPIs (i3D), amoxicillin + lansoprazole (i3E), verapamil + simvastatin + ezetimibe (i4), amoxicillin clavulanic acid + lansoprazole (i5), calcium carbonate + vitamin D + PPIs (i6). Purpose: To evaluate GPs opinions of the efficacy and applicability of the cooperation project between pharmacists and GPs using a questionnaire. Material and methods: Strategies included: verifying the prescribing habits before the project, a literature review, consulting the Codifa database for practical solutions for the management of interactions, monitoring prescriptions in 2012, meetings and the questionnaire which was submitted to GPs. Reports with results obtained were given to the GPs. Results: 75% of the GPs contacted answered the questionnaire. Results were as follows: i) literature analysis was considered interesting by 94%, while 6% did not answer, ii) solutions were useful as follows: 20% i3C, 18% i5, 13% i3A and i3E, 10% i3D, 9% i1, 4% i2, i4, i6, and 1% i3B, while 4% did not answer, iii) clinical improvement after the solutions were applied were observed in 34%, and iv) 80% of patients were satisfied. Such clinical improvements were monitored with blood tests, where possible (i1, i3A, i3C, i4, i6), by 30% of the GPs. 1/36 GPs found ADRs related to the drug interactions. Conclusion: The multidisciplinary approach was effective in increasing GP awareness of drug interactions. Furthermore, we learned of clinical improvements and patients' satisfaction from GP questionnaires. The project is continuing, monitoring prescriptions in 2013 and 2014. References and/or acknowledgements: No conflict of interest.